Assessing the Health Benefits of Physical Activity Due to Active Commuting in a French Energy Transition Scenario - Pierre Barban; Pierre Barban; Pierre Barban; Audrey De Nazelle; Stéphane Chatelin; Philippe Quirion; Kévin Jean; Kévin Jean; Kévin Jean (Frontiers Media S.A., 2022)
Objectives: Energy transition scenarios are prospective outlooks describing combinations of changes in socio-economic systems that are compatible with climate targets. These changes could have important health co-benefits. We aimed to quantify the health benefits of physical activity caused by active transportation on all-cause mortality in the French negaWatt scenario over the 2021-2050 period.Methods; Relying on a health impact assessment framework, we quantified the health benefits of increased walking, cycling and E-biking projected in the negaWatt scenario. The negaWatt scenario assumes increases of walking and cycling volumes of +11% and +612%, respectively, over the study period.Results: As compared to a scenario with no increase in volume of active travel, we quantified that the negaWatt scenario would prevent 9,797 annual premature deaths in 2045 and translate into a 3-month increase in life expectancy in the general population. These health gains would generate €34 billion of economic benefits from 2045 onwards.Conclusion: Increased physical activity implied in the negaWatt transition scenario would generate substantial public health benefits, which are comparable to the gain expected by large scale health prevention interventions.